PEMBERDAYAAN MASYARAKAT MELALUI PEMBENTUKAN KELOMPOK ASUHAN MANDIRI BERBASIS PEMANFAATAN DAUN KELOR UNTUK PENCEGAHAN STUNTING - Dhita Kris Prasetyanti; Putri Wahyu Wigati; Sutrisni; Halimatus Saidah; Meirna Eka Fitriasnani (Universitas Kadiri, 2026)
Stunting is a chronic nutritional condition that affects child growth and development and remains a major public health concern in Indonesia. Community empowerment–based interventions utilizing local food resources, such as moringa leaves, are important strategies for stunting prevention. This community service program aimed to establish a Self-Care Group and to improve the knowledge of mothers of under-five children and community health cadres regarding the use of moringa leaves for stunting prevention. The program was conducted in Sukorejo Village, within the working area of Ngasem Public Health Center, involving 20 participants. The intervention included the formation of a self-care group, nutrition education, and evaluation using pre-test and post-test methods. The results showed that before the intervention all participants had low knowledge, while after the intervention all participants (100%) demonstrated good knowledge. The main outcome was the establishment of a Self-Care Group to support sustainable, community-based stunting prevention efforts